Strategi Pengembangan Kawasan Bahari Berbasis Masyarakat di Blitar Selatan - Darmawanto, Agus Tri (EP FEB UNS, 2014)
This study aims to (i) To identify and explain the characteristics of the Regional Maritime Region in South Blitar; in each sub-districts are District Bakung District Wonotirto, District Panggungrejo, and the District of Wates; the contributing factors in the region; (Ii) To formulate and establish a Development Strategy for Community-based Marine Region in South Blitar.Object Research District of District Bakung, District Wonotirto, District Panggungrejo, and the District of Wates. This research method using descriptive method. Method of data collection was done by interview and observation. The analytical method used by the SWOT analysis.The results based on (i) Characteristic Maritime Region in Blitar region south of the four sub-district has potential in agriculture, livestock and fisheries. As for some of the obstacles that arise in developing the potential in particular marine owned South Blitar, among others; road infrastructure is still inadequate, public transport reatif little, relatively low rainfall, surface conditions are relatively poor, relatively far distance of the capital and human resources is still low. Therefore, the development potential in the region is still not optimal; (Ii) The strategy needed in developing maritime region, among others; increase the carrying capacity of the infrastructure in order to improve the accessibility of roads, transportation systems, water supply and environmental protection in supporting the development of regional maritime, optimizing the processing of agricultural potential, farming, fishing in the area of maritime creating value-added agricultural production, animal husbandry and fishery., power support in the form of infrastructure and community skills in the processing of agricultural, livestock, fisheries in the marine area still needs to be improved with a model tourism village concept, required negotiations and talks about future land use in the development of the maritime area and create a website to introduce to the public the maritime region Keywords: Natural Resources, Human Resources, Strategy, Development Maritime RegionsJEL Classification: O44, Q56